Metal Implant - Shamsul Baharin, Jamaludin, Prof. Dr; Mazlee, Mohd Noor, Dr.; Che Mohd. Ruzaidi, Ghazali, Prof. Madya; Nurhidayah, Ahmad Zaidi (Malaysian Invention and Design Society (MINDS), 2010)
Prof. Dr. Shamsul Baharin Jamaludin and his team won Bronze for Metal Implant. ITEX 2006, 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.